Peran Orang Tua Terhadap Perilaku Perawatan Gigi Pada Anak Usia Sekolah (6-12 Tahun) Di Dusun Paok Odang Desa Sisik Kecamatan Pringgarata Kabupaten Lombok Tengah - Sutomo, Suswinda Yuli; Usman, Arip; Yulandasari, Vera; Wikandari, Deasi (Universitas Qamarul Huda Badaruddin, 2020)
Teeth and mouth disease incidence amount of Indonesia is still high, it is around 89%. The factor influencing the high of teeth disease is behavior of teeth care. Behavior of teeth care is influenced by many factors, one of them is the role of parent. The purpose of this research is to identify the correlation between the role of parent and behavior of teeth care on school aged children (6-12 years old). This research design was descriptive correlation with cross sectional approach. The population was all of object in the research as many as 71 respondents. Sample of this research was the parent who have school aged children (6-12 years old) namely 71 respondents and sampling technique used Total sampling. Data analysis using bivariate analysis using Spearman Rank test. Result of research shows the most of parent’s role in sufficient category as many as 43 (60.5%), and most of children’s teeth care behaviour is in sufficient category 35 (49.3%). Result of data analysis by Spearman Rank test is obtained correlation-value τ = 0.000 with p-value (0.548) < α (0.05) ( Ho was rejected). there is correlation between the role of parent and behavior of teeth care on school aged children (6-12 years old) with moderate relationship strength. It means the better the role of parents in guiding the children’s the better the behavior of dental care in children. Based on result of the research, it is suggested to parent to increase their role to ward behavior of teeth care of children.